Private Responses for Public Sharing: Understanding Self-Presentation and Relational Maintenance via Stories in Social Media - Trieu, Penny; Baym, Nancy (CHI 2020, 2020)
With nearly two billion users, social media Stories-an ephemeral format of sharing-are increasingly popular and projected to overtake sharing via public feeds. Sharing via Stories differs from Feeds sharing by removing the visible feedback (e.g. "likes" and "comments") which has come to characterize social media. Given the salience of responses visibility to self-presentation and relational maintenance in social media literature, we conducted semi-structured interviews (N = 22) to explore how people understand these processes when using Stories. We find that users have lower expectations for responses with Stories and experience lower pressure for self-presentation. This fosters more frequent sharing and a sense of daily connectedness, which strong ties can find valuable. Finally, the act of viewing takes on new significance of signaling attention when made known to the sharer. Our findings point to the importance of effort and attention in understanding responses on social media.